Formulasi Transdermal Patch Nanoemulgel Ekstrak Dadap Serep (Erythrina subumbrans (Hassk.) Merr.) dan Rimpang Kencur (Kaempferia galanga L.) sebagai Kandidat Laktagogum Herbal Berbasis Usadha - Ni Luh Gde Mona Monika; Ella Yunita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Traditional Usadha-based herbal lactagogues, such as Erythrina subumbrans and Kaempferia galanga, are used by lactating mothers; however, their delivery in practical, standardized forms is limited. This study aimed to formulate a nanoemulgel transdermal patch containing E. subumbrans extract and K. galanga extract, evaluate its physicochemical properties, and assess its safety for skin irritation as a potential herbal lactagogue. Extracts of E. subumbrans and K. galanga were added to the nanoemulsion base. The nanoemulsions were incorporated into HPMC/PVP-based transdermal patch matrices by solvent casting. The resulting patches were evaluated for physicochemical properties and tested for skin irritation. Phytochemical screening confirmed the presence of flavonoids, tannins, triterpenoids, saponins, and alkaloids in both extracts. The total flavonoid contents were 47.44 mg QE/g for E. subumbrans and 36.79 mg QE/g for K. galanga. The nanoemulsion exhibited greater than 90% transmittance, mean droplet size of 7.79 nm, and polydispersity index (PDI) of 0.193. The patches met acceptable physical criteria, including a thickness of 0.20 mm, weight variation with %CV less than 10%, and folding endurance over 300. pH values ranged from 6.00 to 6.58. In a human patch test, no erythema or edema was observed; only mild pruritus (mean = 0.2) was reported in two participants. The formulated nanoemulgel transdermal patches demonstrated favorable physicochemical properties and were non-irritating. These patches show potential as a herbal lactagogue delivery system; further studies on lactation efficacy and long-term stability are recommended.